An Overview of the Potentials of Artificial Intelligence Tools in Foreign Language Teaching - Alina Bruckner; Alexandra Chiriac (Linguaculture)
This paper intends to examine the potential uses and applications of artificial intelligence (AI) technology in the field of foreign language didactics. Starting from an overview of the current state of artificial technology, this paper proceeds to present and analyze some of the most well-known AI tools and applications available today, focusing particularly on their potential uses and benefits in the foreign language course. Even though the primary emphasis is placed on the way in which AI tools could significantly enhance both the learning and teaching experience, the authors also address the inherent limitations and challenges that such tools and applications currently pose. The paper discusses various issues, such as technical difficulties, accessibility concerns, and the need for human oversight. In addition, the authors consider the necessity of redefining not only the structure and content of foreign language courses, but also the evolving role of the teacher in an AI-integrated educational environment, suggesting that while AI can offer substantial support, the teacher’s role remains indispensable for providing contextualized guidance, emotional support, and personalized feedback.